The effect of referral for cardiac rehabilitation on survival following acute myocardial infarction: a comparison survival in two cohorts collected in 1995 and 2003. (February 2014) - Lewinter, Christian; Bland, John M; Crouch, Simon; Doherty, Patrick; Lewin, Robert J; Køber, Lars; Hall, Alistair S; Gale, Christopher P
Background: International guidelines recommend referral for cardiac rehabilitation (CR) after acute myocardial infarction (AMI). However, the impact on long-term survival after CR referral has not been adjusted by time-variance. We compared the effects of CR referral after hospitalization for AMI in two consecutive decades. Methods and results: A total of 2196 and 2055 patients were recruited in the prospective observational studies of the Evaluation of the Methods and Management of Acute Coronary Events (EMMACE) -1 and 2 in 1995 and 2003, (1995: median age 72 years, 39% women, 74% referred vs 2003: median age 71 years, 36% women, 64% referred) and followed up through September 2010. Survival functions showed CR referral to be an independent predictor for survival in 2003, but not in 1995 (hazard ratio (HR), 0.90; 95% confidence interval [CI]; 0.70 to 1.17, p = 0.44 in 1995 vs HR, 0.80; 95% CI, 0.66 to 0.96, p = 0.02 in 2003) when patients entered the model at three months after discharge and had a common exit at 90 months. Significant positive and negative predictors for CR referral were beta-blocker prescription (+), reperfusion (+) and age (−) in 1995, and reperfusion (+), revascularization (+), heart failure (HF) (+), antiplatelets (+), angiotensin-converting-enzyme inhibitor (ACE-I) (+), statins (+), diabetes (−), and the modified Global Registry of Acute Cardiac Events (GRACE) risk score (−) in 2003. Conclusions: CR referral was associated with improved survival in 2003, but not in 1995 in patients admitted with acute MI.